Graft copolymers based on Poly(2-(dimethylamino)ethyl methacrylate) and Poly(ethyleneimine): synthesis and evaluation as vectors for DNA transfection (2020)
The first chapter reviews the most important aspects of the polymeric vectors used in gene therapy. This type of therapy involves the introduction of genetic material into specific cells to treat certain diseases, using vectors that mediate the cellular internalization of nucleic acids and protect them from degradation. Synthetic cationic polymers have shown promising results as gene vectors, due to their advantages such as higher safety, simple fabrication process and modifiable structure. Poly(ethyleneimine) (PEI) and poly(2- (dimethylamino)ethyl methacrylate) (PDMAEMA) have been highlighted in this context due to their high transfection efficiency; however, the non-biodegradable character and associated cytotoxicity have limited their applications. To overcome these disadvantages, several researchers have studied the implementation of strategies such as PEGylation, copolymerization with hydrophobic segments and the use of branched architectures, which have demonstrated to significantly reduce the toxicity and increase the transfection efficiency. In addition, these structural modifications can be perform using synthetic methods, such as controlled polymerizations and selective coupling reactions, which allow the design of molecules with well-defined properties. The second chapter describes the synthesis and characterization of copolymers composed of methoxy poly(ethylene glycol) and a hydrophobic block of poly(ɛ-caprolactone-co-propargyl carbonate) grafted with low molecular weight PDMAEMA or linear PEI (lPEI), using a combination of ring opening polymerization, click chemistry and atom transfer radical polymerization. In this way, materials with different grafting densities and lengths of the hydrophobic segment were obtained. Following the proposed synthetic route, the synthesis of graft copolymers based on PDMAEMA with target structure and composition was achieved, while for copolymers composed of lPEI, lower grafting densities than the target ones were obtained. These materials could self-assembled in aqueous medium to form positively charged particles with average sizes between 150 and 380 nm. The third chapter covers the formation and characterization of the copolymer/DNA complexes with different nitrogen/phosphorus (N/P) ratios and complexation matrices. The study of the condensation ability showed that all PDMAEMA copolymers were able to complex the DNA molecules at N/P ratios ≥ 1, regardless of the used conditions, while lPEI copolymers required N/P ratios from 7 to 20, depending on their composition and the complexation solution. In the case of the materials composed of PDMAEMA, the measurements of particle size and zeta potential indicated the formation of positively charged complexes with sizes below 300 nm, which are suitable for cellular uptake. On the other hand, the lPEI based complexes exhibited negative or neutral surface charges with hydrodynamic diameters below 500 nm. These physicochemical properties could generate restrictions for the effective delivery of DNA. The fourth chapter describes the in vitro cytotoxicity of graft copolymers and the transfection efficiency of the resulting polyplexes, using 25 kDa lPEI and 20 kDa PDMAEMA as controls. The copolymers were less cytotoxic to L929 cells than the control homopolymers, exhibiting higher cell viability by reducing the length of the hydrophobic segment and the amount of cationic grafts. Polyplexes formed from PDMAEMA copolymers were more efficient in the delivery of DNA in HEK-293 cells than the standard polycations, without affecting the cell viability. On the other hand, the complexes based on lPEI copolymers exhibited a low transfection efficiency, even using high polymer concentrations and N/P ratios. In general, copolymers composed of long hydrophobic segments and higher grafting density showed a better performance. In particular, the material PP6D5 showed the most promising features for its application as DNA transfection agent, for both in vitro and in vivo assays. This thesis represents the starting point for future research related to the rational design of grafted structures based on cationic polymers that may have improved properties and performance for their application as gene delivery systems.